AKU DAN âYANG LAINâ MENGAMINI PERBEDAAN, MERANGKAI PERSATUAN - Atasoge, Anselmus D (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
The harmony of diversity in religion-ethnic-culture- is the dream of allpluralistic Indonesian components. Dialogue is one possibility as well as ahope to make unity in diversity towards harmony despite of the pessimisticfeelings that there is no truly ideal dialogue and interfaith meeting happen.The ideas and examples in this paper open up the optimistic feelings behindthe pessimism. That is, when âothersâ becomeâ friendsâ to be trusted, whenpersonal assumptions are changed and âMeâ and âOthersâ recognize themistakes of each other in history that have passed through historical motions,and whenâ Meâ andâ Others âcan move beyond dialogue to work together in asociety with its beginnings and small ways. At that point thatâ Me âandâ othersâcan overcome the history that has divided âmeâ and âthe otherâ into two worldsby line different sharp demarcation.